Guidance for the Formation of Spiritual Character of Sekami Children at the Stasi Santo Joseph Freinademetz - Tibo, Paulinus; Pakpahan, Alek Martin; Simanjuntak, Ubania; Ginting, Ema Br; Simalango, Cahaya (PT FORMOSA CENDEKIA GLOBAL, 2024)
Community service is an integral part of the mission of the Santo Bonaventura Pastoral College in shaping the spiritual character of SEKAMI children at the Stasi Santo Joseph Freinademetz, Bandar Setia. This program involves students in weekend pastoral activities using lecture, question and answer, and modeling methods. The main objective of this service is to help SEKAMI children understand and internalize spiritual characters in everyday life. The program evaluation showed a significant increase in the understanding and application of spiritual values ​​in SEKAMI children, reflected in their attitudes and actions. This structured approach has succeeded in bringing significant positive impacts in shaping the character of SEKAMI children through direct interaction and active learning. As a recommendation, it is necessary to strengthen and expand the program with an inclusive and in-depth approach to support the spiritual and moral growth of SEKAMI children in a sustainable manner.